Faktor-Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Manufaktur Di BEI - Hizkia Budiansyah, Ardiansyah Rasyid (Jurnal Paradigma Akuntansi, 2019)
This study aims to understand the theory of  firm size, financial leverage, institutional ownership, income smoothing, and to determine whether firm size, financial leverage, and institutional ownership partially and simultaneously affect income smoothing at manufacturing companies in Indonesia Stock Exchange (IDX) 2015-2017. Sampling using purposive sampling technique and total data used in this research is as many as 62 companies. The test results separately show partially financial leverage has a negative effect on income smoothing, while for firm size, and institutional ownership has no effect on income smoothing. Based on the test results simultaneously note that firm size, financial leverage, and institutional ownership simultaneously have an effect on income smoothing